2023
DOI: 10.3390/coatings13020371
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Compression Molding Temperature on VOCs and Odors Produced from Natural Fiber Composite Materials

Abstract: In the automotive sector, the use of nonwoven preforms consisting of natural and thermoplastic fibers processed by compression molding is well known to manufacture vehicle interior parts. Although these natural fiber composites (NFCs) have undeniable advantages (lightweight, good life cycle assessment, recyclability, etc.), the latter release volatile organic compounds (VOCs) and odors inside the vehicle interior, which remain obstacles to their wide deployment. In this study, the effect of the compressing mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…There were no real changes in the chemical composition with the molding temperature, but the material obtained at 240°C had a higher water-soluble extractable content. It has been shown that increasing the temperature from 180°C to 240°C should increase furfural release [47]. In our case, the water-soluble extractable content increase in the materials could have been linked to hemicellulose degradation into residual sugars, which could in turn be converted into sugar degradation products, such as furfural.…”
Section: Effect Of Molding Temperaturementioning
confidence: 66%
See 1 more Smart Citation
“…There were no real changes in the chemical composition with the molding temperature, but the material obtained at 240°C had a higher water-soluble extractable content. It has been shown that increasing the temperature from 180°C to 240°C should increase furfural release [47]. In our case, the water-soluble extractable content increase in the materials could have been linked to hemicellulose degradation into residual sugars, which could in turn be converted into sugar degradation products, such as furfural.…”
Section: Effect Of Molding Temperaturementioning
confidence: 66%
“…Materials should be manufactured with a MC that allows to exceed the lignin glass transition temperature so as to promote its mobilization and plasticization, thereby improving self-bonding of the material and its final properties [63]. The improvement in mechanical properties observed when MC increased from 0 to 7.2% could be also explained by the higher material density obtained, the improvement in heat transfer [47], the contribution of water to bonding via hydrogen bonding [18] and capillary sorption between particles among the fibers [63]. Increasing MC to > 7.2% led to a steady decline in the mechanical properties, in accordance with previous results [20,64].…”
Section: Effect Of Moisture Contentmentioning
confidence: 99%
“…This may involve introducing functional groups [ 17 ] and changing the molecular weight [ 18 ] and crystalline structure [ 19 ] of the polymer. Various treatments such as extrusion [ 20 ], injection molding [ 21 ], compression molding [ 22 ], and filament winding [ 23 ] can be used to shape and enhance the properties of polymer materials. Furthermore, the addition of nanoparticles [ 24 ] or nanotubes [ 25 ] to polymer composites can significantly improve their mechanical, thermal, and electrical properties [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the great demands of the chemical industry and real-time gas monitoring systems, high sensitivity and good stability of gas sensors are attracting tremendous attention. SnO 2 , ZnO, and WO 3 have always been the traditional and dominant materials for sensor fabrication [1][2][3][4][5][6]. However, the excellent stability, long-cycles, and low detection limit of the sensors still face the challenge, especially working at a high temperature above 200 • C. At higher temperatures, the inevitable grain growth of materials would degrade the sensor stability and life [6].…”
Section: Introductionmentioning
confidence: 99%